Backstroke start kinematic and kinetic changes due to different feet positioning - de Jesus, Ka.; de Jesus, Ke.; Figueiredo, P.; Gonçalves, P.; Matheus Pereira, S.; Vilas-Boas, J. P.; Fernandes, R. J. (Journal of Sports Sciences, 2013)
The backstroke swimming start international rules changed in 2005. This study compared two backstroke start variants, both with feet parallel to each other but in complete immersion and emersion. Six elite swimmers performed two sets of 4 maximal 15 m bouts, each set using one of the variants. The starts were videotaped in the sagittal plane with two cameras, providing bi-dimensional dual-media kinematic evaluation, and an underwater force plate and a handgrip instrumented with a load cell collected kinetic data. Backstroke start with feet immerged displayed greater centre-of-mass horizontal starting position, centre-of-mass horizontal velocity at hands-off and take-off angle. Backstroke start with feet emerged showed greater wall contact time, centre-of-mass horizontal and downward vertical velocity at take-off, lower limbs horizontal impulse, and centre-of-mass downward vertical velocity during flight phase. Backstroke start with feet immerged and emerged displayed similar centre-of-mass horizontal water reach, back arc angle and 5 m starting time. Irrespective of the swimmer`s feet positioning, coaches should emphasise each variant`s mechanical advantages during the wall contact phases. Furthermore, the maintenance of those advantages throughout the flight should be stressed for better backstroke start performance.